Colonic Lamina Propria Inflammatory Cells from Patients with IBD Induce the Nuclear Factor-E2 Related Factor-2 Thereby Leading to Greater Proteasome Activity and Apoptosis Protection in Human Colonocytes. Issue 11 (November 2016) - Kruse, Marie-Luise; Friedrich, Martin; Arlt, Alexander; Röcken, Christoph; Egberts, Jan-Hendrik; Sebens, Susanne; Schäfer, Heiner
Abstract : Background: The antioxidant transcription factor Nrf2 confers broad cytoprotection and has a dual role in tumorigenesis. Enhancing proteasome activity is one mechanism by which Nrf2 can promote cancer development, e.g., colorectal cancer. This study investigated whether this potential oncogenic effect of Nrf2 emerges already from the epithelial adaptation to persistent oxidative stress during inflammatory bowel disease (IBD). Methods: Reactive oxygen species (ROS)–producing inflammatory myeloid cells (IMCs) from colon tissue of patients with IBD were cocultured with human NCM460 colonocytes. ARE-luciferase-, c-H2 DCF-DA-assays, Western blotting, and quantitative polymerase chain reaction were performed for assessing Nrf2-activity, intracellular ROS-level, and Nrf2-target gene expression. Proteasome activity was quantified by Suc-LLVY-amido-4-methylcumarin-assay, and apoptosis by caspase-3/-7 assay and PARP1-Western blots. Nrf2, proteasome proteins, and IMCs were analyzed in IBD-tissues by immunohistochemistry. Results: IMC-coculture caused a temporary increase of ROS in NCM460, followed by Nrf2 activation and elevated expression of ROS-protecting enzymes (NQO1, GCLC). This was accompanied by Nrf2-dependent expression of proteasome proteins (PSMD4, PSMA5) and an enhanced proteasome activity in IMC-cocultured NCM460. Nrf2-siRNA or the ROS-scavenger Tiron blocked these alterations. Depending on Nrf2-induced proteasome activity, IMC-cocultured NCM460 or Colo320 cancer cells were less sensitive to apoptosis (TRAIL-/etoposide induced). Immunostaining of IBD-tissues confirmed Nrf2 activation in the colonic epithelium within inflamed areas, along with greater proteasome protein expression. Conclusions: IMC/NCM460-coculture experiments and immunohistochemistry of colonic tissues from patients with IBD reveal a Nrf2-dependent adaptation of colon epithelial cells to oxidative stress caused by inflammatory cells. This involves increased proteasome activity and apoptosis resistance that protect from tissue damage due to colitis on one hand, but on the other hand, may favor carcinogenesis. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 21 September 2016.